A global value chain (GVC) model for determining changes in global output caused by currency appreciation. Issue 4 (18th May 2020) - Zhao, Yongliang; Fei, Xiaohui; Wu, Chenxing; Hashmi, Shabir Mohsin
ABSTRACT: This study used a global value chain model to determine the effect of currency appreciation and its resultant impact on different sectors, value chains, and world output. Based on the global value chain (GVC) perspective, we derived a formula for the computation of world output adjustment by sectors caused by currency appreciation. Utilizing the WIOD database, we applied the formula to calculate the changes to the value-added by each sector level, given a specified currency appreciation. Our empirical findings revealed that currency appreciation creates an illusion of higher GDP growth when denominated in a foreign currency. However, when denominated in domestic currency, appreciation of the currency put an adverse impact on its own GDP growth. The impact of currency appreciation varies from country to country and their respective sectors. Taking the world as a whole, US dollar exchange rate appreciation drives up global real GDP, while RMB appreciation leaves a negative impact on the global GDP. Furthermore, it is assumed that if a country's aggregate demand exceeds its aggregate output, its currency appreciation tends to expand global GDP. Similarly, if a country produces more than what it consumes, its currency appreciation leads to decline in the global GDP.